The Crime of Murder by a Child as the Perpetrator A Criminal Psychology Perspective - Nurani Rizki Anandia (LOCUS MEDIA PUBLISHING, 2022)
The purpose of this study is to examine and analyze several issues regarding the legal arrangements for the settlement of criminal acts of murder committed by children, the causes of criminal acts of murder committed by children in the perspective of criminal psychology, and criminal policy in law enforcement of criminal acts of murder against children who commit criminal acts of murder. The background is because the diversion mechanism for children who commit murder is difficult to reach an agreement, so that in the end the trial in court becomes the last resort and in the end the child ends up in the Children's Correctional Institution. Although the trial uses the juvenile criminal justice system with a restorative justice approach in every implementation, in reality there are still many law enforcement officials, both judges, prosecutors and police who still view a child in committing a crime as being blamed for his actions without looking at the aspects that occur both from within and outside the child. The results showed that the criminal act of murder committed by children was more due to external factors from the environment and family around the perpetrator, although diversion is very difficult to reach an agreement between the victim and the perpetrator so that very often the perpetrators of criminal acts of murder committed by children end up in prison, but judges still have to seek diversion and restorative justice as a form of protection for children. In terms of sentencing, judges are given the freedom to look at the law, jurisprudence, legal science or doctrine and the factors that cause crimes committed by children, both internal and external factors. However, in practice judges use only the written law in determining sentences or are limited to the prosecutor's indictment.